DIGITALISASI SISTEM PENGARSIPAN DOKUMEN UNTUK MENINGKATKAN EFISIENSI ADMINISTRASI PADA SEKRETARIAT DAERAH KABUPATEN BOJONEGORO - Siti Shoimah; Ahmad Sholikin; Nawari; Bagas Satrio Wibowo; Febrian Helmi (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
The rapid development of information technology encourages government institutions to improve administrative efficiency through digital transformation. One important aspect of administrative management in government institutions is document archiving. Conventional archiving systems that rely on physical document storage often lead to various problems, such as document accumulation, difficulties in retrieving information, and the risk of document damage or loss. This community service activity aims to improve the understanding and skills of administrative staff in implementing digital archiving systems at the Social Welfare Division (KESRA) of the Regional Secretariat of Bojonegoro Regency. The methods used in this activity include observation, training, practical digital document processing, and administrative assistance. The results of the activity indicate that the implementation of digital archiving improves document management efficiency, accelerates document retrieval processes, and creates a more systematic and secure document storage system. In addition, digital archiving also reduces the accumulation of physical documents and improves workspace organization. Therefore, digitalization of archives becomes a strategic step in supporting effective and efficient administrative governance in government institutions.